Natur – Geschichte – Schreibung - Die Grenzsituation der Naturalis Historia von Plinius dem Älteren - Darab, Ágnes (Acta Classica Universitatis Scientiarum Debreceniensis, 2025)
According to the preface, Pliny’s Natural History belongs to the genre of historia, of which subject is the nature. At the same time, the preface offers other genre classifications as well: encyclios paideia, thaesaurus. Pliny himself points out the novelty of his work: Libros naturalis historiae […] novicium opus (praef. 1.). Regarding Pliny’s peculiar concept of nature, in terms of the genre and literary history, Natural History can be interpreted as a borderline case.